ASTROMETRIC CCD OBSERVATIONS OF SELECTED WDS MULTIPLE STAR SYSTEMS - Maigurova, N. V.; Protsyuk, Yu. I.; Bondarchuk, L. E. (Одеські астрономічні публікації, 2018)
Main objective of the study is getting information about multiple and double stars that allow us to determine whether this pair is physically link system. Physically bounded star systems are source of unique information such as the ratio of the periods of pairs in one system, the relative orientation of the orbital planes, the distribution of components by mass which is extremely important for determining the parameters of star formation models and for testing stellar models evolution. The results of selected multiple star systems CCD observations, which were carried out at the KT-50 telescope of the Research Institute “Mykolaiv Astronomical Observatory” during the 2016-2018 years are presented. The Washington catalog of double stars (WDS) was used for observational list. There were presented detailed study of 14 multiple star systems. Astrometric reductions of the CCD frames with multiple system components at the current epoch were performed using “Astrometrica” software with Gaia DR2 reference catalog. The combination of the CCD received data with other Strasbourg base catalogs allowed to determine the new values of stars proper motions. Parameters of mutual component configuration (position angle and separation) were also measured for the components of the multiple star systems using REDUC software. The measures standard errors were 0.05" for separations and 0.2° for position angles. Combination ground based original observations with accurate astrometric catalogs available due to Strasbourg astronomical Data Center allowed us obtain new knowledge about investigated objects.